INJURIES TO THE PRIMARY TEETH AND SOFT TISSUES IN CHILDREN IN NIS, SERBIA - Igić, Ana; Stojkovic, Branislava; Mitic, Aleksandar; Acovic, Aleksandar; Todorovic, Kosta; Todorovic, Ana; Sokolovic, Dusan; Igic, Marija (Acta medicae Medianae, 2021)
The aim of this study was to analyze injuries to the primary teeth and adjacent soft tissues in relation to the gender and age of injured children, type of injury, place, and mechanism of injury. The study enrolled 115 children (71 boys and 44 girls) managed at the Dentistry Clinic, Faculty of Medicine University of Niš, in the period 2009-2019. The information about the type of injury, place, and mechanism of injury were obtained from the medical records of the patients aged 1-5 years. Our analysis established that there were statistically significantly (p<0.05) more injured boys (61.74%) than girls (38.26%). Subluxation was the most common primary teeth injury, present in 60 (52.17%) children and was statistically significantly more prevalent compared to other injuries (p<0,001). Of the injuries to the adjacent soft tissues, laceration was statistically significantly more common than other soft tissue injuries (p<0.001). Children were most commonly injured in their homes (52.17%), and rarely in their day nurseries (3.48%). Falling was the most common cause of injuries (63.48%). Based on the obtained results, a conclusion may be drawn that boys were more commonly injured compared to girls, and that falls were the most common cause. Injuries usually occurred at the age of about 2 years. Subluxation was the most common injury, and children usually got injured in their own home.